Terra sigillata from Aquincum-Viziváros (Water Town) - Gabler, Dénes (Rei Cretariae Romanae Fautorum Acta, 2012)
The earliest Danubian fort of eastern Pannonia was built on the territory of Budapest i, Vizivaros. according to military historical data, the ala fort fulfilled an important role in the second half of the 1st century at the end of a radial road that connected italy with the Danube. Close to 2.500 sigillata vessels have been published from the capital of the later Pannonia inferior since the 1870s, but due to historical reasons of research, most of them came from the territories of the legionary fortress established in aD 89and the attached canabae. the number of finds published from the buildings of the civil town, the municipium and later the colonia (centre of the fire brigade, gas factory, pottery shop, basilica) in comparison is low and the few sigillata vessels from the civil town do not allow a comparative analysis. Unfortunately it cannot be determined, if the ceramics taken to museums and sometimes published in the late 19th and the early 20th century were found in the civil town or on Obuda, the canabae legionis, and the material of the excavations conducted in the civil town in the 1960s has not yet been published. thus the majority of the published terra sigillata, 1.757 items, originates from the territory of the canabae legionis where numerous rescue excavations were conducted from the 1930’s up to 2003.